Automatic Change Detection of Emotional and Neutral Body Expressions: Evidence From Visual Mismatch Negativity - Ding, Xiaobin; Liu, Jianyi; Kang, Tiejun; Wang, Rui; Kret, Mariska E. (Frontiers in Psychology, 2019)
Rapidly and effectively detecting emotions in others is an important social skill. Since emotions expressed by the face are relatively easy to hide, we often use body language to gauge the real emotional state of others. Recent studies suggest that expression-related visual mismatch negativity (vMMN) reflects the automatic processing of emotional changes in facial expression; however, the automatic processing of changes in body expression has not yet been studied systematically. The current study uses an oddball paradigm where neutral body actions served as standard stimuli, while fearful body expressions and other neutral body actions served as two different deviants to define body-related vMMN, and to compare the mechanisms underlying the processing of emotional changes to neutral postural changes. The results show a more negative vMMN amplitude for fear deviants 200-250 ms after stimulus onset which corresponds with the negativity bias that was obtained on the N190 component. In earlier time windows the vMMN amplitude following the two types of deviant stimuli are identical. Therefore, we present a two-stage model for processing changes in body posture, where changes in body posture are processed in the first 170-200 ms, but emotional changes in the time window of 200-250 ms.